Code-Mixing in Cinta Laura’s Podcasts - Malo, Arnonce; Artawa, Ketut; Sri Rahayuni, Ni Ketut (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 25 No 1 (2025), 2025)
The aims of this research are to identify the types of code-mixing and the factors involved in Cinta Laura's utterances in her YouTube podcasts. Data were collected from Cinta Laura's podcasts using the document analysis method and field note techniques. This research analyzed the data using the content analysis method, and the results are presented using an informal method and descriptive technique. To analyze the types of code-mixing, this research used Muysken’s theory (2000), and for the factors of code-mixing, it used the theory proposed by Bhatia and Ritchie (2006). The results found 43 instances of insertion, 36 instances of alternation, and 10 instances of congruent lexicalization. Additionally, four factors influencing code-mixing in the podcasts were identified: participant roles and relationships, situational factors, message-intrinsic factors, and language attitudes, dominance, and security.